Antibody durability is influenced by interleukin-2 production by undifferentiated memory T helper cells and extensive B cell clonal expansion - Isogawa, Masanori; Shinoda, Masahiro; Kotaki, Ryutaro; Terahara, Kazutaka; Onodera, Taishi; Kabasawa, Kiyomi; Toyama-Kousaka, Mio; Fujisawa, Mizuki; Watanabe, Mitsukaze; Tonouchi, Keisuke; Terooatea, Tommy; Kitano, Ayumi; et al. (Cell reports (Cambridge), 2025)
SARS-CoV-2-neutralizing antibody titers serve as immune correlates of protection against COVID-19; however, the durability varies among vaccinees. Here, we demonstrate that the durability of vaccine-boosted antibody responses is closely correlated with the pre-booster capacity of spike-reactive CD4+ T cells to produce interleukin (IL)-2 and T helper type 2 (Th2) cytokines. IL-2 production by CD4+ T cells was also associated with extensive B cell clonal expansion, which preceded the durable antibody responses. High-dimensional cytometric and transcriptomic analyses revealed that IL-2-producing CD4+ T cells exhibit low expression of markers characteristic of circulating T follicular helper cells or peripheral helper T cells. Nonetheless, IL-2-producing T cells highly express key helper molecules such as CD40L, ICOS, and IL-21, along with the transcription factor BACH2, which is known to prevent T cell differentiation and senescence. Thus, our study indicates a potential role of undifferentiated memory T helper cells in orchestrating the durability of antibody responses. [Display omitted] •Post-booster neutralizing antibodies wane slowly in the sustainer group•IL-2-producing potential in memory T cells differs in the sustainer group•IL-2-producing potential predicts sustained antibody titers at post-booster•IL-2+ T cells are memory Th0 cells expressing BACH2 and helper molecules Isogawa et al. show that antibody durability after booster vaccination is predicted by pre-existing memory T cells that produce IL-2 upon antigen stimulation. These memory T cells, termed memory Th0 cells, uniquely express BACH2, distinguishing them from conventional helper T cells.